Analyzing the Representation of Ganbaru Values in Anime Blue Period through Roland Barthes' Semiotic Approach - Lestari, Herlindadwi; Andreas, Rino (Jogjakarta Communication Conference (JCC), 2025)
Anime is a mass communication media that influences conveying a cultural message to the audience, so anime can show a country's culture. This study aims to analyze the representation of the ganbaru value contained in the character Yatora Yaguchi and how the anime can be an inspirational tool for the audience. This research seeks to identify how ganbaru values are packaged through signs, symbols, and audiovisuals. In this study, the researcher used a descriptive qualitative method and analyzed using Roland Barthes' semiotic theory. The sample used was purposive sampling, where data collection was carried out based on criteria relevant to the study. Based on the study's results, Yatora Yaguchi shows ganbaru values as follows: 1.) Hard Worker, 2.) Fighting to the Last Breath, 3.) Determined to Find a Solution and 4.) Never Give Up. There are also positive effects, such as not giving up easily, and negative effects from the pressure to high standards. With this analysis, it can be understood that the Yaguchi character is a representation of the form of ganbaru values in culture in Japanese society.